THEORETICAL-METHODOLOGICAL ELEMENTS IN THE SEARCH OF NEW DIRECTIONS FOR PHYSICAL EDUCATION IN EARLY CHILDHOOD EDUCATION (Fiep Bulletin - online, 2013)
From the reflection about the theory and the pedagogical practice of the Childhood Education, this paper aims to show a deep analysis in the areas of Childhood Education and Physical Education. Through the bibliographical analysis and based on the phenomenology, this paper aims to understand the aspects of child´s development, relevant to correlation between Childhood Education and Physical Education. The work of a Physical Education's professional, according to the studies presented in this paper, seems to be fundamental to the Childhood Education to comprehend that the “Child World” demands to be respected in its pace and in pedagogical spaces which need to be able to provide an emancipator interaction, valuing the “Self-Movement”, the imagination and the act of play with essentials elements of Childhood Education.
Keywords: Childhood Education; Physical Education; Child.